Raspberry pi projects for the evil genius - Norris, Donald (New York : McGraw Hill Education, 2014)
This hands-on resource gives you a guided tour of the Raspberry Pi hardware, operating system, and IDE ... then gets you running with the Python programming language and the GPIO library so you can start on your creations right away. You'll learn how to assemble a prototype board to use with your projects, and then you'll jump right in with illustrated, step-by-step instructions that lead you through projects that gradually grow in sophistication.
Introduction to Raspberry Pi -- LED blinker project -- MP3 player project -- Camera controller -- GPS -- Earthquake detector -- Home automation -- Home security controller -- NFC/RFID reader -- 1-wire weather station -- Local and remote logic controller -- Robotic car -- Radon detector -- Serving up time with an RTC and NTP.
Includes index.
Keywords: RAPSBERRY PI (COMPUTER)